Left in limbo – Experiences and needs among postmenopausal women newly diagnosed with osteoporosis without preceding osteoporotic fractures: A qualitative study. Issue 1 (March 2018) - Jakobsen, Pernille Ravn; Hermann, Anne Pernille; Søndergaard, Jens; Wiil, Uffe Kock; Dixon, Ronald F; Clemensen, Jane
Introduction: Despite the fact that the first osteoporotic fracture is preventable, osteoporosis is still a major health challenge. The disease is highly prevalent among postmenopausal women. However little is known about how to meet and support women, when they are diagnosed with osteoporosis without preceding fractures. Therefore this study aims at gaining a deeper understanding of how women experience being diagnosed. Furthermore to describe and identify their needs, which should be met in future healthcare services. Methods: We conducted a phenomenological qualitative study. We included 17 women aged 52–65 and collected data through semi-structured interviews. We analysed data following Giorgi's methodology. Findings: Needs among the women were classified into three main themes: (1) needs of targeted and tailored information about osteoporosis, (2) needs of being prepared for GP visit to participate in treatment decision-making and (3) needs of being able to take care of bone health. Conclusion and implications: In general the women experienced as been left 'in limbo', and they requested targeted and tailored information about osteoporosis. In particular, they want information about dual-energy X-ray absorptiometry (DXA) scan results and treatment options in advance of the GP visit. This will help them in being prepared and able to participate in treatment decisions. They ask for support in self-management of the disease with less focus on disease and risk of fracture. Instead, they demand more attention on the benefits of detecting early stage osteoporosis. The study highlights the call for new approaches to postmenopausal women newly diagnosed with osteoporosis without preceding fractures.